The Effect of Four Different Activities on Limited Time Recovery - Thongtanaphat, Nataphon (Academic Journal of Thailand National Sports University, 2011)
The purpose of this study was to examine and compare the effects of four different activities on limited time recovery. Sampling groups were twenty male members of football team and were selected by purposive sampling method. The study was composed of four days with in 48 hours rest time between each day. All subjects were received all four activities in a whole period of study. Before starting the experiment, body weight was measured and warmed up for 15 minutes then rested for 5 minutes. Next, the subjects were tested by RAST (Running - based Anaerobic Sprint Test) protocol to examine anaerobic power and anaerobic capacity. Then, all subjects were divided the subjects into 4 groups and gave them 60 seconds recovery time with different methods: sitting, walking, static stretching and cold compression. Finally, they were tested by RAST again at the end of each experiment. For the next three days; repeated the same processes and rearranged the recovery method that gave to each group until completed all four methods. The data were analyzed by using One - Way ANOVA with repeated measurement. Two groups of data were tested by Bonferroni correction. This result showed that. 1. There was no significance in anaerobic power recovery between four activities. 2. There was significance in anaerobic capacity recovery between four activities. Even though, there was no significantly difference in anaerobic power recovery between four activities. However, comparing between four types of those activities, the percentage change of recovery by walking tend to be the most effectively. Moreover, his became obviously show in anaerobic capacity recovery part. In conclusion, walking technique during limited time recovery seem to be more effectively and it could be adapted and use in training period or match day to boost advantages especially in sport that require power or speed endurance.